Daily Step Counts in Relation to Metabolic Syndrome and Lifestyle Behaviors: Findings from a Two-Year Observational Study in Mhealth-Based Healthy Lifestyle Clubs in Cambodia. - Kwon, Eunjoo; Kim, Hyunseung; Hwang, Oknam; Ryoo, Seungwan; Kim, Yukyung; Yang, Youngran (Research in Community & Public Health Nursing (RCPHN), 2026)
Purpose: This study aimed to investigate the relation between daily step counts, metabolic health, and lifestyle practices among participants in a healthy lifestyle club in Cambodia. Methods: A single-group repeated-measures observational design was used to examine temporal changes in metabolic health and health behaviors over a 2-year period. 204 participants were residents aged 40 years or older who enrolled in the project "noncommunicable disease prevention and management program using mHealth in Prek Pnov, Cambodia" in 2022-2024. They were retrospectively categorized as either the low-step volume group(LSG) or the high-step volume group(HSG), based on average daily step counts using the 8,000 steps per day criterion. Metabolic syndrome(MetS) was identified using the Joint Interim Statement criteria. Results: Significant within-group changes in metabolic parameters over 2 years in both groups, including reductions in waist circumference(WC), diastolic blood pressure(DBP), fasting blood glucose(FBG), as well as increases in high-density lipoprotein(HDL) cholesterol. Improvements were also found in the prevalence of MetS, high triglyceride(TG), high BP, and low HDL-cholesterol, and in health behaviors such as regular exercise, daily fruit intake, and reduced sugar-sweetened beverages or artificially sweetened beverages consumption(p<.05). These changes were more pronounced at the 1-year follow-up, with a slight decline at 2-year follow-up. Conclusion: Participation in the mHealth- and peer-supported healthy lifestyle club was associated with favorable changes in metabolic health and health behaviors among Cambodian residents in the program. Continuous engagement in community-based health promotion activities may be more relevant than achieving a specific absolute daily step count.